Traumatic Myelopathy: Current Concepts in Imaging - De Smet, Eline; Vanhoenacker, Filip M.; Parizel, Paul M. (Seminars in Musculoskeletal Radiology, 2014)
Traumatic myelopathy is a frequent complication after spinal trauma. The prognosis is often very poor, and the condition has important socioeconomic consequences. Knowledge of the epidemiology and imaging features is mandatory to ensure correct diagnosis and timely intervention. Imaging studies play an increasing role in the diagnosis and follow-up of this condition. Computed tomography remains the first-line investigation whenever spinal cord injury is suspected. It may indicate the presence of spinal cord lesions by visualizing vertebral lesions, but it cannot assess the spinal cord itself. Magnetic resonance imaging (MRI) can depict possible spinal cord edema, hemorrhage, or transection, and it is essential in diagnosing and predicting the outcome of spinal cord injury. Follow-up should also be performed with MRI to evaluate long-term intramedullary changes. Diffusion-weighted imaging and diffusion tensor imaging are promising new techniques that allow very early detection of spinal cord injury by measuring the diffusion within the spinal cord, thereby providing information on white matter integrity. However, technical limitations of these new techniques prompt further investigation to improve specificity.
Keywords: traumatic myelopathy; radiography; computed tomography; magnetic resonance imaging; spine